Study of Degradation of Norfloxacin Antibiotic and Their Intermediates by Natural Solar Photolysis - Salazar-Gonzalez, R; Toledo-Neira, C; Toledo-Neira, C; Muñoz-Lira, D; Muñoz-Lira, D; Rivera-Vera, C; Rivera-Vera, C (Springer Science and Business Media Deutschland GmbH, 2023)
In this work, the photolysis of the antibiotic norfloxacin (NOR) and the formation of its photodegradation products were studied using UV and solar radiation. Their extraction was also assessed in Milli-Q water and secondary effluents from a wastewater treatment plant. The photolysis of NOR was chromatographically monitored. The structure of each degradation product is related to the reaction of NOR with reactive oxygen species (ROS), as confirmed using radical quenchers and mass spectrometry. Additionally, the feasibility of extracting NOR and its degradation products was assessed using a commercial solid phase extraction system. Photolysis results showed the formation of five degradation products, generated under exposure to both types of radiation. The decays in NOR concentrations for the solar and UV treatments were adjusted to pseudo first-order kinetics with apparent constant values of ksolar = 1.19 × 10−3 s−1 and kUV = 3.84 × 10−5 s−1. Furthermore, the superoxide radical was the main participant species in the formation of the degradation products P3, P4, and P5. Species P1 and P2 do not need this radical for their formation. The presence of NOR in water opens the possibility of its photolysis by solar radiation. This work contributes to the understanding of the mechanisms that mediate its photodegradation, in addition to studying potential options for its determination and its photodegradation products in the sample treatment. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Norfloxacin antibiotic; Solid-phase extraction; Photodegradation products; High-performance liquid chromatography-mass spectrometry; Solar radiation; UV radiation